Integrating Confucianism for a More Holistic Approach to Teaching Sustainability - Guo, Mengyuan (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2026)
This article explores the integration of Confucian principles into adult education for sustainability (EfS) to foster a more holistic understanding of sustainability that bridges Eastern and Western perspectives. Drawing on the philosophical teachings of Confucianism and their relevance to contemporary global challenges, the article highlights how Confucian concepts such as qi (气); the Triad of Heaven, Earth, and Humanity; and the five constant virtues can inform and enhance sustainability education. By examining the intersections of Confucianism, adult education, and sustainability, the article underscores the potential of Confucianism to contribute to a sustainable future through moral self‑cultivation, ecological ethics, and the development of a harmonious relationship with nature. The article also discusses how Confucian teachings can be integrated into the curriculum and pedagogical approaches of EfS, promoting lifelong learning and the development of just and sustainable learning environments globally. Through this exploration, the article aims to offer new insights into the role of traditional wisdom in addressing contemporary sustainability challenges and advancing global EfS.